About democracies and exclusions. Notes on a future that was not - Yuing-Alfaro, Tuillang (Re-presentaciones: Periodismo, comunicación y sociedad, 2023)
The investigation is about the margins of institutionality and political actions. Is a simultaneous question for the place of passion in politics delimitated by reason. Agamben and his exception idea serves us like a contribution. The interest is to show how different ways of political participation are debtors of exclusion and its rationality. The delegative excercises are then contrasted with the political gestures of the multitude, according to Farge´s and Revel´s conception. The text evaluates these political gestures according to the judgment of the institutional order. Finally, the text interprets the period of Chilean democratic transition, which is considered as a process that establishes the framework for a type of governability and for the current political participation.
Keywords: Exclusion; Democracy; Political Passion; Democratic transition